Identification of a novel heterozygous germline RAD52 missense mutation in a patient with gallbladder carcinoma: A case report - Zhao, Wenhu (Medicine (Baltimore), 2021)
RATIONALE: Gallbladder carcinoma is a malignant biliary tract tumor which is characterized by poor prognosis. Recent advances in genomic medicine have identified a few novel germline mutations that contribute to the increased risk of gallbladder carcinoma. RAD52 is a crucial human deoxyribonucleic acid (DNA) repair gene involved in maintaining genomic stability and preventing tumor occurrence. PATIENT CONCERNS: A 57-year-old man was hospitalized for space-occupying lesions in the gallbladder. DIAGNOSIS: A diagnosis of gallbladder adenocarcinoma was made based on computed tomography, B-ultrasound, blood tests, and postoperative pathology. INTERVENTIONS: Next-generation sequencing using a 599-gene panel and Sanger sequencing were performed to validate the mutation in the proband and his family members, respectively. OUTCOMES: A novel potentially pathogenic heterozygous germline RAD52 missense mutation (c.276T > A: p.N92K) was identified in the patient. Sanger sequencing revealed that this variation was not observed in unaffected family members. LESSONS: We identified a novel heterozygous germline RAD52 missense mutation in a patient with gallbladder carcinoma. Our results added to the current body of knowledge. It also provides new insights into genetic counseling and targeted therapeutic strategies for patients with gallbladder carcinoma.